2017
DOI: 10.1097/qad.0000000000001469
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery endothelial dysfunction is present in HIV-positive individuals without significant coronary artery disease

Abstract: Objective HIV+ individuals experience an increased burden of coronary artery disease (CAD) not adequately accounted for by traditional CAD risk factors. Coronary endothelial function (CEF), a barometer of vascular health, is depressed early in atherosclerosis and predicts future events but has not been studied in HIV+ individuals. We tested whether CEF is impaired in HIV+ subjects without CAD as compared to an HIV- population matched for cardiac risk factors. Design/Methods In this observational study, CEF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Two previous studies found that MLWH with low CVD risk have MFRs comparable to HIV-uninfected men [ 16 , 30 ]. On the other hand, a recent study of PLWH both with and without CAD found that PLWH (63% men) without CAD had coronary endothelial function, as assessed by coronary MRI, comparable to HIV-uninfected patients with CAD, with no obvious influence of sex [ 31 ]. These studies used different imaging modalities, including cardiac stress testing protocols, which arguably could lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies found that MLWH with low CVD risk have MFRs comparable to HIV-uninfected men [ 16 , 30 ]. On the other hand, a recent study of PLWH both with and without CAD found that PLWH (63% men) without CAD had coronary endothelial function, as assessed by coronary MRI, comparable to HIV-uninfected patients with CAD, with no obvious influence of sex [ 31 ]. These studies used different imaging modalities, including cardiac stress testing protocols, which arguably could lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vivo studies demonstrate the vasomotor response to IHE is primarily mediated by nitric oxide [20] and therefore, reflects endothelial function [6,[21][22][23][24][25]. The feasibility of the IHE-MRI technique to assess vasomotor reactivity in coronary arteries has been studied in patients with coronary artery disease as well as patients with HIV [18,21,26]. Phantom study results suggest that radial MRI is capable of distinguishing area differences in the order of 0.2-0.3 mm 2 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Beside drugs, several pathophysiological alterations potentially contributing to the increased CVD risk have been reported in association with HIV‐1 infection. For instance, HIV‐1 infected patients are characterized by increased oxidative stress , endothelial/vascular dysfunction and platelet activation , again all factors potentially contributing to the atherosclerotic burden in HIV‐1 patients .…”
Section: Introduction: Cardiovascular Disease Risk In Hiv‐1 Infectionmentioning
confidence: 99%